2006
DOI: 10.1111/j.1365-2516.2006.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital factor VII deficiency: therapy with recombinant activated factor VII – a critical appraisal

Abstract: Summary. Congenital factor VII (FVII) deficiency is a rare bleeding disorder with high phenotypic variability, and optimal management has yet to be determined. Treatment has traditionally involved FVII replacement therapy using fresh frozen plasma, prothrombin complex concentrates or plasma-derived FVII concentrates. Recombinant activated FVII (rFVIIa, NovoSevenÒ), the first recombinant treatment option, has recently been approved in the European Union for use in congenital FVII deficiency, but has been availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 40 publications
5
92
1
Order By: Relevance
“…22 Because rhFVIIa has a short half-life, approximately 3 hours in humans, repeated administration, every 4-6 hours, may be necessary to control severe bleeding. 21 Administration of rhFVIIa to FVII-deficient research Beagles at dosages of 5 mg/kg and 30 mg/kg (single IV dose) resulted in transient near normalization of the PT and cuticle bleeding time. n Studies are needed to determine whether rhFVIIa can be used safely and cost effectively (approximately $1,300 per 1.2-mg vial) to supplement or replace plasma components for controlling clinical bleeding in FVII-deficient dogs.…”
Section: Discussionmentioning
confidence: 99%
“…22 Because rhFVIIa has a short half-life, approximately 3 hours in humans, repeated administration, every 4-6 hours, may be necessary to control severe bleeding. 21 Administration of rhFVIIa to FVII-deficient research Beagles at dosages of 5 mg/kg and 30 mg/kg (single IV dose) resulted in transient near normalization of the PT and cuticle bleeding time. n Studies are needed to determine whether rhFVIIa can be used safely and cost effectively (approximately $1,300 per 1.2-mg vial) to supplement or replace plasma components for controlling clinical bleeding in FVII-deficient dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Each case requires individual management because of the poor correlation between F7 mutations, FVII activity, and phenotype (7 ). The patient's bleeding history, current clinical situation, and an FVII activity assay performed with recombinant human thromboplastin must guide initial management of FVII deficiency (8,9 ) (Fig.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…Literature on preoperative treatment protocol is scarce as FVIId comes under rare bleeding disorders. Moreover, the available data are not consistent [5,8,13]. Mariani et al [14] in her study reported of using rFVIIa successfully in seven patients of severe FVIId who underwent major surgeries.…”
Section: Discussionmentioning
confidence: 93%
“…Mean dose/procedure ranged from 13.85 to 26.29 μg/kg and the number of doses/procedure varied from 30 to 112. Other results from different groups showed that 20 -25 μg/dL of rFVII should be given at every 4 -6 h in combination with tranexamic acid which was seen to be effective in surgical settings for FVIId patients but treatment duration is not well defined [5,8,9,15]. Pharmacokinetic studies of rFVII helped in choosing the dose and time interval between the subsequent infusions, but it is still not defined about minimum requirement for FVII in plasma to attain hemostasis [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation